Seeds of transformative learning and its pedagogical implications on a conference-based university course in environmental and geosciences - Siponen, Joula; Salovaara, Janne J.; Särkelä, Karoliina; Ronkainen, Inka; Veijonaho, Salla; Vesterinen, Veli-Matti; Barrio, Isabel C.; Riuttanen, Laura; Lauri, Katja Anniina (Copernicus Publications, 2026)
In this study, we explore students' learning experience during a university course in which students studying environmental and geosciences attend the Arctic Circle Assembly conference, introducing them to a wide range of stakeholders and viewpoints from geopolitical to Indigenous perspectives. Using qualitative methods, we studied the students' sense of belonging and transformativeness of the learning process and how those might influence the development of the students' professional identity. In situ interviews, written reflections of the students, and in-depth interviews after the course reveal elements of the transformative learning process, in which the students' sense of belonging played a role: lack of belonging to the expert community induced dilemmas and belonging to the student group enabled joined reflection. However, some dilemmas do not seem to lead to transformation. Therefore, as pedagogical implications of our findings, we highlight the importance of the facilitation of critical reflection and discourse of the learner's values and beliefs. Facilitation should consider students' prior learning and background and include building of trust and belonging in the learning community, enabling the challenging reflections. We suggest that flexible pedagogies and approaches of transformative climate change education have potential to mould students' professional identity and widen their perspectives on what it means to be a responsible scientist or expert in the Arctic context. This requires not only a deep knowledge of the physical processes but also an awareness and understanding of the region's complex socio-economic dynamics.